THE EFFECT OF PRICE AND SERVICE QUALITY ON CONSUMER LOYALTY IN THE SEBLAK RONYOK KRUENG GEUKUEH CULINARY BUSINESS - Santia Dewi; Cut Sukmawati; Lisa Iryani; Nur Hafni; Sutriani (PT. Radja Intercontinental Publishing, 2026)
Consumer loyalty is an important factor in ensuring the sustainability of culinary businesses. However, Seblak Ronyok Krueng Geukueh still faces problems related to price transparency and service quality, such as customer complaints regarding the absence of purchase receipts, prices perceived as inconsistent with the amount of toppings received, and slow service during peak hours. Therefore, this study aims to analyze the influence of price and service quality on consumer loyalty at Seblak Ronyok Krueng Geukueh. This study employed a quantitative method with an associative approach. A sample of 100 respondents was determined using the Lemeshow formula with a non-probability sampling technique through purposive sampling. Data were collected through questionnaires, observations, and documentation and analyzed using multiple linear regression analysis. The results showed that price and service quality had a positive and significant effect on consumer loyalty. The price variable obtained a t-value of 4.802 > 1.985, while service quality obtained a t-value of 6.324 > 1.985, with significance values of 0.000. The simultaneous test produced an F-value of 134.128 with a significance value of 0.000, indicating that price and service quality simultaneously had a positive and significant effect on consumer loyalty.